2020
DOI: 10.2478/aiht-2020-71-3318
|View full text |Cite
|
Sign up to set email alerts
|

Chiral separation of beta-blockers by high-performance liquid chromatography and determination of bisoprolol enantiomers in surface waters

Abstract: Beta-blockers are chiral compounds with enantiomers that have different bioactivity, which means that while one is active, the other can be inactive or even harmful. Due to their high consumption and incomplete degradation in waste water, they may reach surface waters and affect aquatic organisms. To address this issue we developed a chromatographic method suitable for determining beta-blocker enantiomers in surface waters. It was tested on five beta-blockers (acebutolol, atenolol, bisoprolol, labetalol and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For example, (S)-propanol and (S)-atenolol are more potent than the corresponding (R)enantiomers. [53,54] To evaluate the feasibility of this approach for the preparation of (S)-TAGEs, the obtained product (S)-1 a (er = 94 : 6) was used as starting material with different phenols as nucleophiles under basic conditions. The reaction was carried out with NaOH in ethanol by modification of a protocol reported by Egri et al for 3-chloropropane-1,2-diol.…”
Section: Entrymentioning
confidence: 99%
“…For example, (S)-propanol and (S)-atenolol are more potent than the corresponding (R)enantiomers. [53,54] To evaluate the feasibility of this approach for the preparation of (S)-TAGEs, the obtained product (S)-1 a (er = 94 : 6) was used as starting material with different phenols as nucleophiles under basic conditions. The reaction was carried out with NaOH in ethanol by modification of a protocol reported by Egri et al for 3-chloropropane-1,2-diol.…”
Section: Entrymentioning
confidence: 99%
“…Plenty of researchers [ 15 , 74 , 75 , 76 , 77 ] chose commercial chirobiotic columns, including teicoplanin containing Chirobiotic T and T2, teicoplanin aglycone containing Chirobiotic TAG, ristocetin A containing Chirobiotic R, and vancomycin containing Chirobiotic V and V2, as their chiral selector for the enantioseparation of β-blockers.…”
Section: Enantioseparation Of β-Blockers By Hplcmentioning
confidence: 99%
“…In the case of β-blockers, the cardiac β-blocking activity generally resides in their S (-) enantiomer [ 11 , 12 , 13 ], and the reported S : R activity ratio ranges from 33 to 530 [ 14 ] due to the diverse degree of binding affinity to the β-receptor. For example, S -propranolol is 100 times more potent than R -propranolol [ 15 ]. Therefore, the separation of racemates of β-blockers is essential both in the laboratory and industry.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, GC [6,7], GC-MS [8,9], CEC [10,11], HPLC [12,13], LC-MS/MS [14,15], and other methods play an important role in the separation of chiral compound. Dong et al [3,5] and Wang et al [16] have reported that triadimenol stereoisomers were successfully separated on Chiral column using HPLC method.…”
Section: Introductionmentioning
confidence: 99%